2015
DOI: 10.1103/physrevlett.114.175001
|View full text |Cite
|
Sign up to set email alerts
|

First High-Convergence Cryogenic Implosion in a Near-Vacuum Hohlraum

Abstract: Recent experiments on the National Ignition Facility [M. J. Edwards et al., Phys. Plasmas 20, 070501 (2013)] demonstrate that utilizing a near-vacuum hohlraum (low pressure gas-filled) is a viable option for high convergence cryogenic deuterium-tritium (DT) layered capsule implosions. This is made possible by using a dense ablator (high-density carbon), which shortens the drive duration needed to achieve high convergence: a measured 40% higher hohlraum efficiency than typical gas-filled hohlraums, which requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…More recent NIF experiments using HDC ablators and hohlraum He fill densities from 0.03 to 0.6 mg/cc are in better agreement with HFM calculations than the earlier CH ablator experiments, but a discrepancy of ∼300 ps or 10% in the peak drive persists 16 . Experiments in which the hohlraum gas fill density was systematically varied up to 1.6 mg/cc showed that for 5.75 mm diameter hohlraums and 2 mm diameter HDC capsules, the bang time discrepancy increases for helium fills above 0.6 mg/cc, 17,18 rising to 800 ps at a fill density of 1.6 mg/cc.…”
Section: Introductionmentioning
confidence: 50%
“…More recent NIF experiments using HDC ablators and hohlraum He fill densities from 0.03 to 0.6 mg/cc are in better agreement with HFM calculations than the earlier CH ablator experiments, but a discrepancy of ∼300 ps or 10% in the peak drive persists 16 . Experiments in which the hohlraum gas fill density was systematically varied up to 1.6 mg/cc showed that for 5.75 mm diameter hohlraums and 2 mm diameter HDC capsules, the bang time discrepancy increases for helium fills above 0.6 mg/cc, 17,18 rising to 800 ps at a fill density of 1.6 mg/cc.…”
Section: Introductionmentioning
confidence: 50%
“…The timeresolved equatorial x-ray emission data for N131212 showed less than 5% swing in symmetry, confirming that the hot spot did not undergo symmetry swings during burn despite the purposefully driven swing in flux symmetry, i.e., these designed symmetry swings in drive did not produce symmetry swings in hot spot emission. 18 Increased case-to-capsule ratio Another option to mitigate hindered inner beam propagation is to design a hohlraum with a larger diameter to increase the distance between the capsule and wall; such a design is currently being experimentally explored. For this series of experiments, the diameter of the hohlraum was increased to 6.72 mm (from the nominal size of 5.75 mm), and the length was increased to 11.26 mm (from 10.13 mm) (Fig.…”
Section: Dynamic Beam Phasingmentioning
confidence: 99%
“…4,6,18 This makes sense: during its development, the high-flux model was bench-marked against vacuum hohlraum experiments performed on the NOVA and OMEGA laser facilities. The first demonstration of the high-flux model's utility for designing NIF experiments was its ability to reproduce x-ray intensity data from vacuum hohlraums, as reported by Olson.…”
Section: Model Adjustmentsmentioning
confidence: 99%
“…19 The high efficiency of near-vacuum hohlraums for driving implosions is described in more detail in a recent paper by Hopkins. 18 The x-ray conversion efficiency g CE % 90% for near-vacuum hohlraums on the NIF. For a given amount of laser energy, a near-vacuum hohlraum can drive a capsule with 30%-40% more x-ray intensity than one filled with helium gas of q տ 1 mg/cm 3 .…”
Section: Model Adjustmentsmentioning
confidence: 99%
See 1 more Smart Citation